Recovery of neutron-irradiated VVER-440 RPV base metal and weld exposed to isothermal annealing at 343°C up to 2,000 h - Altstadt, Eberhard; Bergner, Frank; Brandenburg, Jann-Erik; Chekhonin, Paul; Dykas, Jakub; Houska, Mario; Ulbricht, Andreas (Frontiers in Nuclear Engineering, 2024)
Neutron irradiation causes embrittlement of reactor pressure vessel (RPV) steels. Post-irradiation annealing is capable of partly or fully restoring the unembrittled condition. While annealing at high temperatures (e.g. 475 °C) was successfully applied to extend the lifetime of operating VVER-440 reactors, the benefit of annealing at lower temperatures (e.g. 343 °Cthe maximum to which the primary cooling water can be heated) is a matter of debate. In this study, neutron-irradiated VVER-440 RPV base metal and weld were exposed to isothermal annealing at 343 °C up to 2000 hours. Given the limited amount of material, the degree of recovery was estimated in terms of Vickers hardness, the ductile-brittle transition temperature derived from small punch tests, and the master curve reference temperature derived from fracture mechanics tests of mini samples. For the base metal, small-angle neutron scattering was applied to underpin the findings at the nm-scale. We have found significant partial recovery in both materials after annealing for 300 hours or longer. The variations of the degree of recovery are critically discussed and put into the context of wet annealing.